Comparison of Heat Transfer in the Case of Turbulent Flow Between a Duct Without Ribs and a Duct with Semi-Circular Inner Ribs - قبيلي يامن (Latakia University Journal -Engineering Sciences Series, 2021)
In this research, an experimental model was created to study the effect of adding a semi-circular internal rib inside a square-shaped duct on the heat transfer in case of turbulent flow, and a comparison was made between the air temperature inside the duct before and after adding the ribs. Conditions studied: Reynolds numbers (10460- 40500), air temperature Inlet 25 ℃, the flow is manually changed by the flow control valve. Through experiments, it was found that there was an improvement in the heat transfer of the duct equipped with circular ribs compared to the duct without a rib at a rate ranging between (10.87-28.13) %.